2017
DOI: 10.1002/hep.29324
|View full text |Cite
|
Sign up to set email alerts
|

A liver‐specific gene expression panel predicts the differentiation status of in vitro hepatocyte models

Abstract: Alternative cell sources, such as three‐dimensional organoids and induced pluripotent stem cell–derived cells, might provide a potentially effective approach for both drug development applications and clinical transplantation. For example, the development of cell sources for liver cell–based therapy has been increasingly needed, and liver transplantation is performed for the treatment for patients with severe end‐stage liver disease. Differentiated liver cells and three‐dimensional organoids are expected to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 40 publications
3
47
0
1
Order By: Relevance
“…The inferred CNV profiles are consistent with the CNV profiles in HCC and iCCA from previously published studies (Chaisaingmongkol et al, 2017;Katoh et al, 2007;Roessler et al, 2012). We further confirmed the successful enrichment of malignant and non-malignant cells based on the epithelial marker genes and liver marker genes, which differ in their expression between malignant cells and stromal cells (Kim et al, 2017;Puram et al, 2017). The expression of these marker genes is highly concordant with the karyotypes of malignant cells and non-malignant ones ( Figure 1E).…”
Section: Single-cell Transcriptomic Profiling Of Patient-derived Primsupporting
confidence: 89%
“…The inferred CNV profiles are consistent with the CNV profiles in HCC and iCCA from previously published studies (Chaisaingmongkol et al, 2017;Katoh et al, 2007;Roessler et al, 2012). We further confirmed the successful enrichment of malignant and non-malignant cells based on the epithelial marker genes and liver marker genes, which differ in their expression between malignant cells and stromal cells (Kim et al, 2017;Puram et al, 2017). The expression of these marker genes is highly concordant with the karyotypes of malignant cells and non-malignant ones ( Figure 1E).…”
Section: Single-cell Transcriptomic Profiling Of Patient-derived Primsupporting
confidence: 89%
“…A comparison study to detect possible paracrine effects (unknown soluble factors) from populated spheroids on CYP3A4 activity was performed and did not show any significant differences between the group used in this study and a group with fewer spheroids (three spheroids in one conical tube, i.e., 15 ml volume; Figure S7) during the differentiation culture period. The heat map analysis of the liver‐specific gene expression panel (LiGEP) illustrated the high shear stress‐elevated differentiation level of the 3D HepaRG spheroids (Figure f(i); Kim et al, ), and also showed the shear stress dependence of Phase I and II enzyme gene expression; overall high in SFU, intermediate in OS, and low in static mode (Figure f(ii,iii)). CYP3A4 is the most important Phase I enzyme related to drug metabolism, with various CYP3A4 activity‐related factor‐binding sites existing in the promoter region (Figure f(iv)).…”
Section: Resultsmentioning
confidence: 95%
“…After 2-3 wk, hESC-like hiPSC colonies were selected and subsequently expanded for further characterization. Fibroblasts and hiPSCs were cultured as previously described (13,14).…”
Section: Methodsmentioning
confidence: 99%